Pengaruh Lama Perendaman Bawang Putih (Allium sativum L.) terhadap Kualitas Organoleptik Telur Asin Itik - Darmawati, Darmawati; Zulfiadi, Zulfiadi (MACROCEPHALON : Jurnal Ilmu Peternakan, 2025)
This study aimed to evaluate the effect of garlic soaking duration on the organoleptic quality of salted duck eggs. Garlic (Allium sativum L.) contains bioactive compounds such as allicin, diallyl disulfide, and phenolic compounds that act as natural antimicrobial and antioxidant agents, thereby potentially improving the sensory quality of salted eggs. The experiment was conducted using a Completely Randomized Design (CRD) with four soaking duration treatments: P0 (without garlic soaking), P1 (10 days), P2 (15 days), and P3 (20 days), each with three replications. A total of 60 duck eggs were used in this study. The soaking solution was prepared from a mixture of water, salt, and garlic, with the garlic amounting to 20% of the salt weight. After soaking, the eggs were steamed for 30 minutes and then subjected to organoleptic testing by 15 semi-trained panelists on four sensory parameters—color, aroma, texture, and taste—using a 1–5 hedonic scale. Data were analyzed using ANOVA and followed by Duncan’s Multiple Range Test (DMRT) when significant differences were observed (P<0.05). The results showed that the duration of garlic soaking had a highly significant effect (P<0.01) on all organoleptic parameters. Panelists’ preference scores decreased with increasing soaking duration. Treatments P1 (10 days) and P2 (15 days) produced sensory scores that were still well accepted by the panelists, whereas P3 (20 days) resulted in a significant decline in color, aroma, and texture. It can be concluded that garlic soaking duration significantly affects the organoleptic quality of salted duck eggs, with an optimal duration of 10–15 days to achieve the best sensory characteristics.